Cytophotometric Determination of Intraspecific Variation of DNA per Cell in Pinus banksiana - Landauer, Kurt (University of Wisconsin-Stevens Point, 1977)
Intraspecific DNA variation among 16 provenances of Pinus banksiana was demonstrated cytophotometrically with chicken erythrocyte nuclei used as an internal standard. The measured factor of increase was 1.18. The use of a single source of pine nuclei as an'internal standard was also evaluated and the pine nuclei cannot be recommended for internal reference without careful testing, since extreme variation in DNA amounts was observed. The use of chicken erythrocyte nuclei as an internal standard is recommended.